THE EFFECT OF TERA EXERCISE ON REDUCING ANXIETY LEVELS IN THE ELDERLY IN WONOHARJO VILLAGE, BUMI AGUNG DISTRICT, WAY KANAN LAMPUNG - Pamungkas, Putri; Sumardiko, Dwi Setiani; Hidayatullah, Ariska Putri; Nur Cahyanto, Heri (Journal of Vocational Nursing, 2024)
Introduction: Anxiety is a feeling of fear that is not clear and is not supported by the situation. Usually, anxiety or anxiety disorders will be accompanied by behavioral, emotional, and physiological changes (Kaliman, 2011) Anxiety in the elderly if not handled properly then the anxiety will have an impact on increasing mental disorders. Therefore, Tera exercise therapy is needed which is expected to reduce anxiety in the elderly  Methods: The method in this study is a quantitative research type with a quasi-experimental research design with a pretest post-test control group approach. The sample in this study was the elderly who suffered from anxiety as many as 36 respondents who met the inclusion criteria. Collecting data in the study using a questionnaire sheet and data analysis using the Wilcoxon rank test statistical test. Results: The results of the Wilcoxon sign rank test with SPSS for Windows with a significance level of = 0.05 obtained a P value = 0.001 (0.001 <0.05) then Ho is rejected which means there is an effect of Tera exercise on decreasing anxiety levels in the elderly in Wonoharjo Village, Bumi Agung District, Way Kanan Lampung. Conclusions: For elderly who experience anxiety ranging from severe, moderate, and mild levels using tera exercise therapy can reduce anxiety levels in the elderly because it can cause them elderly to relax, feel comfortable, and happy, and interact with other elderly people.